Compact two-element transmission trap detector for 1550 nm wavelength. (31st March 2015) - Vaigu, Aigar; Kübarsepp, Toomas; Manoocheri, Farshid; Merimaa, Mikko; Ikonen, Erkki
Abstract: We have developed and characterized a new kind of trap detector based on InGaAs photodiodes. The detector contains only two 10 mm diameter InGaAs photodiodes arranged in a transmission trap configuration with non-coaxial beam orientation. The detector has large active area, more than 9 mm in diameter, and a built-in linearity monitoring feature. One of the key advantages of the developed detector is polarization insensitivity—the difference in responsivity between two orthogonal incident polarization states is zero within the standard uncertainty of 0.3%. The spatial non-uniformity of the responsivity is less than 0.5% across the active area.